2020
DOI: 10.1002/ejoc.201901923
|View full text |Cite
|
Sign up to set email alerts
|

Similarity and Competition between Biginelli and Hantzsch Reactions: an Opportunity for Modern Medicinal Chemistry

Abstract: Similarity and competition between multicomponent reactions with similar mechanisms and leading to similar scaffolds can be a useful tool for medicinal chemistry. In this review, we have summarized the studies disclosing the mechanism of such competition between the Biginelli and Hantzsch reactions. We focused our attention in particular on those studies exploiting similarity and competition as an opportunity to switch from one reaction to another, by simply changing the reaction conditions, thus opening the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 105 publications
0
16
0
Order By: Relevance
“…The varied activity of DHPMs, combined with their synthetic accessibility and the possibility to rapidly assemble diverse substituents on the heterocyclic scaffold in a single multicomponent reaction, make the Biginelli reaction an attractive approach for the discovery of new biological activities. Multicomponent reactions, in particular, show great promise in the discovery of small molecule protease inhibitors possessing better pharmacological properties than peptidomimetic inhibitors [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The varied activity of DHPMs, combined with their synthetic accessibility and the possibility to rapidly assemble diverse substituents on the heterocyclic scaffold in a single multicomponent reaction, make the Biginelli reaction an attractive approach for the discovery of new biological activities. Multicomponent reactions, in particular, show great promise in the discovery of small molecule protease inhibitors possessing better pharmacological properties than peptidomimetic inhibitors [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism is confirmed by the literature. [56] In order to highlight the competency of the present developed procedures, we have compared our results obtained from the synthesis of ethyl 2,7,7-trimethyl-5-oxo-4-(4-meth-ylphenyl)-1,4,5,6,7,8-hexahydroquinoline-3-carboxylate and 9-(4-chlorophenyl)-3,3,6,6-tetramethyl-3,4,6,7,9,10-hexahydroacridine-1, 8-(2H,5H)-dione in the presence of PNSS with the same results obtained using other catalysts as reported in the literature. Based on the Table 4, it can be concluded that our new method interestingly can resolve some disadvantages in terms of long reaction times (Table 4, entries 1-8 and 16-18), high catalyst loading (Table 4, entries 6,8,10,11 and 18), use of expensive reagent (Table 4, entries 9,10), harsh reaction conditions (Table 4, entries 1,3,5,6), moisture sensitivity of the catalyst (Table 4, entries 12) and in-ability to produce a wide range of derivatives (Table 4, entries 3,7,10,13,14).…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Although they are known for more than a century, the use of MCRs experienced an enormous growth in the last decades due to their many advantages and new clever designs to "guide" the final output. [18][19][20][21][22] Many reviews are currently available dealing with a myriad of different features of MCRs and their specificities, [23][24][25][26][27][28][29][30][31][32][33][34][35] yet they have shown that the field is not at all exhausted and still many avenues are still open for new creative strategies, efficiency improvements and synthetic applications. [36] A huge gap to develop more efficient MCRs is the limited information of their reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%